1998
DOI: 10.1183/09031936.98.12051164
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of inhaled nitric oxide in adult respiratory distress syndrome

Abstract: In patients with adult respiratory distress syndrome (ARDS), inhaled nitric oxide (NO) may both reduce pulmonary hypertension and improve arterial oxygenation [1,2]. The NO-induced decrease in pulmonary artery pressure depends on the selective pulmonary vasodilating effect of inhaled NO [3], while the NO-induced increase in arterial oxygenation is related to the redistribution of pulmonary blood flow to well-ventilated lung areas, which results in improved ventilation to perfusion matching [1,4]. Although pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 29 publications
(52 reference statements)
0
13
0
2
Order By: Relevance
“…Regarding MPAP, we observed only a small, although significant decrease, which may be due to individual differences in the response to the single dose of 10 ppm NO used in our investigation. In clinical routine, a dose-response study is usually performed prior to the treatment with inhaled NO to reveal the dose with the best impact on gas exchange and pulmonary artery pressure [25,26,27,28]. Intravascular NO is known to be rapidly bound to Hb, which is transformed to MetHb in the presence of oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding MPAP, we observed only a small, although significant decrease, which may be due to individual differences in the response to the single dose of 10 ppm NO used in our investigation. In clinical routine, a dose-response study is usually performed prior to the treatment with inhaled NO to reveal the dose with the best impact on gas exchange and pulmonary artery pressure [25,26,27,28]. Intravascular NO is known to be rapidly bound to Hb, which is transformed to MetHb in the presence of oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Doses of iNO much greater than those used clinically do not cause significant methemoglobinemia in adults. 58 In work we have published we did not observe methemoglobin above 2% of total hemoglobin.…”
Section: Precautions and Adverse Effectsmentioning
confidence: 73%
“…Abman et al, in 1994, 34 described beneficial effects on oxygenation, PH and cardiac index in children with the syndrome. Later, studies conducted on adults 35,36 and children, 37,38 while confirming the immediate beneficial effects, were not capable of demonstrating a prolonged response to iNO therapy. Dobyns et al, 39 however, observed a prolonged response to iNO as compared to therapy with a placebo in subgroups of patients; those with the most serious respiratory failure (oxygenation index > 25) and among immunodepressed patients.…”
Section: Acute Respiratory Distress Syndromementioning
confidence: 99%
“…Abman et al, em 1994 34 , descreveram efeitos benéficos do gás sobre a oxigenação, HP e índice cardíaco em crianças com a síndrome. Posteriormente, estudos conduzidos em adultos 35,36 e em crianças 37,38 , enquanto confirmaram os efeitos benéficos imediatos, não foram capazes de demonstrar resposta prolongada da terapia com NOi. No entanto, Dobyns et al 39 observaram resposta prolongada ao NOi versus terapia com placebo em subgrupos de pacientes, aqueles com insuficiência respiratória mais grave (índice de oxigenação > 25) e nos pacientes imunodeprimidos.…”
Section: Hipertensão Pulmonar Persistente E Insuficiência Respiratóriunclassified
“…Níveis acima de 2% do total de hemoglobina podem prejudicar a liberação do oxigênio e piorar a hipóxia tecidual. Doses de NOi muito maiores do que aquelas usadas clinicamente não causam metemoglobinemia significante em adultos 58 . Nos trabalhos que publicamos não observamos metemoglobina acima de 2% do total de hemoglobina.…”
Section: Precauções E Efeitos Adversosunclassified